Control of molecular aggregation in symmetrically substituted pi-conjugated bulky poly(p-phenylenevinylene)s and their copolymers - Resmi, R.; Amrutha, S. R.; Jayakannan, M. (Journal of Polymer Science Part A-Polymer Chemistry, 2009)
A new series of symmetrically substituted bulky PPV-copolymers based on poly(bis-2,5-(2-ethylhexyloxy)-1,4-phenylenevinylene) (BEH-PPV) bearing tricyclodecane (TCD) pendants were synthesized to study the effect of chain aggregation in the pi-conjugated polymer backbone. The composition of the copolymers was varied up to 100 mol % and the structures of the copolymer were confirmed by NMR and FTIR. The molecular weights of the copolymers were obtained as M(w) = 11,500-1,78,800 depending on the TCD-incorporation in BEH-PPV. The origin of the pi-aggregation was investigated using mixture of solvents (polar or nonpolar) or temperature as external stimuli. Absorption, photoluminescence, and time-resolved fluorescence decay techniques were employed as tools to trace molecular aggregation in solution and solid state. The TCD-substituted bulky copolymers showed almost twice the enhancement in photoluminescence compared with that of BEH-PPV Solvent-induced aggregation studies of copolymers revealed the existence of strong molecular aggregation in BEH-PPV compared with that of bulky copolymers. Variable temperature studies further evidence for the reversibility of molecular aggregation on beating/cooling cycles and showed isosbetic points with respect to free and aggregated polymer chains. Time-resolved fluorescent studies confirmed the existence of free and aggregated pi-conjugated species with a life time of 0.1 to 1.0 ns. (C) 2009 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 47: 2631-2646, 2009
Keywords: conjugated polymers; fluorescence; poly(p-phenylenevinylene); solution properties; Structure-property relationship